Integration of South Africa’s financial markets : focus on equity, foreign exchange and bond markets (2012)
M.Comm. === This study investigates the extent to which South African financial markets are globalised and thus, during the period 1994–2008, integrated with global financial markets. The impact of globalisation on the South African economy is complex. South Africa re-entered the international economy from isolation at a time when the forces of globalisation, especially for developing countries, seemed to gain momentum. The following study focus on equity, foreign exchange and bond markets. The period under study is divided between 1994-2008 and 2000-2008, with the exception of the bond market where the data was challenging to source. Empirical evidence suggests that South African financial markets together with those in emerging economies became increasingly globalised during the period 1994–2008. Analysis finds that South Africa’s equity markets were integrated as common/global factors influenced the markets during the period 1994-2008. According to the findings, SA was even more integrated than the average emerging economies in our sample as global/common factors influenced more of SA equity returns than in emerging economies. However, in general, developed economies were more globalised in both periods under study. However, analysis indicates that common factors play a larger role in determining the fluctuations in the foreign exchange market rather than in equity markets. This implies that foreign exchange markets are more globalised and integrated than equity markets. Global factors only determined 48% of the movement South Africa’s currency during the period 1994-2008, while global factors were more significant in the movement of developed and emerging economies’ currencies during the same period. However, SA foreign exchange market’s integration into the global markets increased with 2000-2008 variance share increasing to 0.97, implying that global factor were responsible the 97% of the variation in the exchange rate – higher than the average variance share recorded for developed and emerging economies. Finally, results for the bond markets show that SA bond market was also closely integrated with global markets although the level of integration was less than that recorded in the foreign exchange rate markets during the 2000-2008.